Ipomoea batatas as a novel binding agent for hot-set restructured binding systems and green coffee bean for improved lipid oxidative stability and storage quality. Issue 5 (11th September 2017) - Dilnawaz, H.M.; Kumar, Sunil; Bhat, Z.F.
Abstract : Purpose: This paper aims to to explore the possibility of utilization of Ipomoea batatas as a novel binding agent for hot-set restructured meat products. Further, green coffee bean (GCB) extract was used as a natural ingredient to improve the lipid oxidative stability and storage quality of the developed restructured mutton blocks. Design/methodology/approach: Restructured mutton blocks were used as a model and were prepared by incorporating different levels of I. batatas, namely, 1, 3 and 5 per cent and analyzed for various quality parameters. Restructured mutton blocks containing optimum level of I. batatas were further treated with GCB (1 per cent) extract as a natural ingredient and assessed for various lipid oxidative stability and storage quality parameters under refrigerated conditions (4 ± 1°C). Findings: Restructured mutton blocks containing 3 per cent level of I. batatas were optimized as best on the basis of various quality parameters. Although a significant declining trend was observed in the sensory characteristics with storage; however, the products containing GCB extract showed significantly ( p < 0.05) higher acceptability. The mean scores for overall acceptability for products with GCB extract on day 0 was 7.4 ± 0.1 and for control was 7.3 ± <0.1. Significantly ( p < 0.05) lower thiobarbituric acid reacting substances (TBARS, mg malonaldehyde/kg) and free fatty acid (FFA, % oleic acid) values were observed for the products containing GCB extract. The mean TBARS and FFA values for products with GCB extract on day 0 were 0.2 ± <0.1 and 0.08 ± <0.1 and for control were 0.3 ± <0.1 and 0.09 ± <0.1, respectively. The restructured mutton blocks containing GCB extract also showed significantly ( p < 0.05) lower values for various microbiological characteristics like total plate count (log cfu/g) and psychrophilic count (log cfu/g). Originality/value: The results showed herein indicate a promising industrial application of I. batatas (3 per cent) as a binding agent for restructured meat products and GCB extract (1 per cent) as a novel natural ingredient for improved lipid oxidative stability and storage quality.